2009
DOI: 10.1590/s0100-736x2009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Microrganismos patogênicos, celularidade e resíduos de antimicrobianos no leite bovino produzido no sistema orgânico

Abstract: RESUMO.-Nos últimos anos cresce a preocupação dos consumidores quanto à qualidade do leite e às condições de produção e bem-estar dos animais. Simultaneamente, aumenta o interesse e o consumo de produtos e subprodutos de origem animal produzidos no sistema orgânico, com destaque para o leite e derivados. O presente estudo investigou a presença de microrganismos patogênicos, a sensibilidade e a multi-resistência dos isolados aos antimicrobianos, a celularidade e a presença de resíduos de drogas no leite de vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 11 publications
2
12
1
20
Order By: Relevance
“…However, because CNS are the major mastitis causing agents in small ruminants, the high frequency of resistant genes in such species reported here is worth noting. Although goats and sheep are raised on pasture in extensive or semi-intensive production systems in Brazil, the widespread use of some antimicrobials for clinical treatment purposes might be associated with the high resistance rates (Ribeiro et al 2009, Schmidt et al 2009), as observed in the present study. Uncontrolled antimicrobial usage was reported by farmers and agricultural technicians in the sampling region.…”
Section: Discussionmentioning
confidence: 51%
“…However, because CNS are the major mastitis causing agents in small ruminants, the high frequency of resistant genes in such species reported here is worth noting. Although goats and sheep are raised on pasture in extensive or semi-intensive production systems in Brazil, the widespread use of some antimicrobials for clinical treatment purposes might be associated with the high resistance rates (Ribeiro et al 2009, Schmidt et al 2009), as observed in the present study. Uncontrolled antimicrobial usage was reported by farmers and agricultural technicians in the sampling region.…”
Section: Discussionmentioning
confidence: 51%
“…Bovine mastitis is caused mainly by bacterial agents, most common of which are those belonging to the genera Staphylococcus spp., Streptococcus spp., and Corynebacterium spp. (13) In a study of milk produced in an organic production system, Ribeiro (9) isolated mainly Staphylococcus spp. and Streptococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…(4) The term 'organic' refers to animal and plant foods produced without the use of fertilizers, pesticides, insecticides, antimicrobials, antiparasitics, transgenics, or any other drug having residues harmful to human health, including products for agricultural use intended for dairy animals. (9) The aim of this study was to develop and test a Schinus terebinthifolius Raddi-based product, with antibacterial action to be used in pre-and post-milking teat antisepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al (2004) também evidenciaram reduzida sensibilidade e especificidade para o CMT no diagnóstico de mastite em caprinos. Tal resultado poderia encontrar justificativa na alta celu- mésticos exploradas com finalidade leiteira em manejo orgânico, pode encontrar justificativa nas mazelas adquiridas do uso indevido destes fármacos, em propriedades que foram recentemente certificadas de convencionais para orgânicas (Ribeiro et al 2009). Entre os métodos profiláticos de mastites, encontrase a utilização de produtos desinfetantes e higienizantes.…”
Section: Resultsunclassified
“…As propriedades orgânicas devem gerar alimentos de alta qualidade nutricional, isentos de resíduos ou de produtos químicos nocivos ao homem (Brasil 2008). Com efeito, o valor agregado do produto orgânico é superior ao leite e subprodutos produzidos de forma convencional, fato que tem motivado a migração de produtores tradicionais para a modalidade orgânica, vislumbrados com esta alternativa de produção de leite e derivados de alto valor econô-mico, sem a necessidade de grandes investimentos (Ribeiro et al 2009). …”
Section: Introductionunclassified